Unified Storage File Format for Additive Manufacturing - Roller, Dieter (2016)
For Additive Manufacturing (AM) the product development process (PDP) differs from traditional, subtractive manufacturing with respect to additional process steps like positioning and slicing. Additionally the file formats necessary for communication with 3D printers are different from CAM files. They are often vendor specific and lack precision compared to the original CAD drawings. One intermediate file format is STL (STereoLitography), a tessellated representation of the original geometry with reduced geometrical information. In the PDP for AM multiple files are created. This includes files such as original CAD drawings, log files, slicing information and Numerical Code (NC) files. The need for archiving and consolidation of these files arises for reasons such as post-processing (e.g., removal of support structures), repeatability, error detection and research. We develop with this research an integrated file format that aggregates and integrates all files from the PDP. This work investigates what different types of information are created throughout the AM PDP, how it can be stored and retrieved efficiently, and how the format can be defined to be extensible for future use cases. The goal of this research is to develop a meta-file format that aids in accumulating all relevant data throughout the creation of parts fabricated or prototyped using AM without replacing or substituting existing file formats.